En el proceso enseñanza-aprendizaje de movimientos de los cuerpos en una dimensión y su incidencia en el logro de aprendizajes significativos en los estudiantes de primer año de bachillerato general unificado de la unidad educativa, anexa el material didáctico un recurso pedagógico a la Universidad Nacional de Loja, período 2012-2013. Lineamientos alternativos - Chalán Herrera, Álvaro Marcel (2014)
The use of training materials for the teaching of physics requires a pedagogical, didactic and scientific view on the part of teachers, in order to inform the teacher about the design and management of teaching materials is born this research whose objectives are: Investigate the theoretical knowledge that teachers have on learning materials in the teaching and learning of movements of bodies’ process in one dimension and its impact on the achievement of significant learning in the freshman general baccalaureate unified educational unit annexed to the National University of Loja 2012-2013. Determine the educational materials used by teachers in the teaching and learning of movements of bodies in one dimension and its influence on the achievement of significant learning in students of first year high school general education unit unified process attached to the National University of Loja 2012-2013. Develop an alternative proposal for a possible solution to achieve significant learning through the teaching and learning of movements of bodies in one dimension, in freshman general education school unified unit, attached to the National University of Loja process. Research is character, descriptive, explanatory and purposeful, we used the following methods: Statistical method for tabulation, analysis and interpretation of results, in addition to the preparation of charts and graphs. The analytical, I use it for the analysis of theoretical information and empirical data. The hypothetical deductive, use it to verify the hypothesis by contrasting the empirical data with the theoretical elements of research. The scientist, this method allowed to approach problems and know the reality of education, using a logical and positive solution to the problem tracing approach. Deductive, I use from conception of the research project, as it is part of general assumptions go check for individual cases. Synthetic allowed drawing conclusions and alternative guidelines to address the problem. The techniques used are the survey with his instrument the questionnaire applied to teachers and students identified above. The statistical technique was used for tabulation of data and ordering tables and graphics and processing the information obtained from the application of the instruments. The technique of the literature review when developing the literature review. It can establish some results, such as: The teaching materials used by teachers have low scientific and pedagogical support. The faculty is managed under a traditional view of education. Teachers are not able to train students with critical , creative and proactive mentality which leads to a disjointed process of reality prevents motivate the student in the classroom , establish a specific relationship of the parts of a subject and all develop meaningful learning , humanism and solidarity with nature.